Method for preparing oxide-type ceramic fabric composite solid electrolyte using EDTA-modified cotton cloth as sacrificial template

The preparation of oxide-type ceramic fabric composite solid electrolyte through EDTA modified cotton templates solves the problems of low energy density, poor safety and difficulty in flexibility of traditional lithium-ion batteries, and achieves high conductivity and mechanical flexibility, which is suitable for flexible lithium batteries.

CN116031478BActive Publication Date: 2025-04-25ZHEJIANG SCI-TECH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211642449.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-20
Publication Date
2025-04-25
Estimated Expiration
2042-12-20

AI Technical Summary

Technical Problem

Traditional lithium-ion batteries have problems such as low energy density, poor safety and difficulty in achieving flexibility, especially liquid electrolytes are flammable and easy to leak, and there are only a small amount of hydroxyl groups on the pure cotton cloth, which cannot adsorb metal ions well.

Method used

Using EDTA modified cotton cloth as a sacrificial template, oxide-type ceramic fabrics are prepared by impregnating the metal ion precursor liquid of the oxide-type ceramic fabric and calcining, and combined with organic polymer solid electrolyte to form a composite solid electrolyte.

Benefits of technology

It improves lithium ion conductivity, enhances electrochemical performance and mechanical flexibility, and is suitable for the application of flexible solid lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116031478B_ABST
    Figure CN116031478B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of energy storage devices, and relates to a method for preparing a material for an energy storage system device, and in particular to a method for preparing an oxide-type ceramic fabric composite solid electrolyte using EDTA-modified cotton cloth as a sacrificial template. The present invention first activates the cleaned cotton cloth with an aqueous NaOH solution, then grafts amino groups on the surface of the cotton cloth with a silane coupling agent APTES, and then performs EDTA modification on the cotton cloth. Finally, a certain type of oxide-type ceramic fabric metal ion precursor solution is prepared; the modified cotton cloth is impregnated with the precursor solution, and an oxide-type ceramic fabric is obtained after high-temperature calcination; finally, a polymer electrolyte of a "polymer conductive lithium salt" system is poured to obtain an oxide-type ceramic fabric composite solid electrolyte. The material can be used in flexible solid-state lithium batteries and has good electrochemical properties and mechanical flexibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of energy storage devices and relates to a method for preparing energy storage system device materials, in particular to a method for preparing an oxide-type ceramic fabric composite solid electrolyte using EDTA-modified cotton cloth as a sacrificial template. Background Art

[0002] The rapid development of wearable electronics, electric vehicles, and smart grids requires energy storage devices with high energy density, high safety, and good mechanical flexibility. After decades of development, lithium-ion batteries have become the mainstream energy storage device for today's electronic products. However, traditional commercial lithium-ion batteries use graphite as the negative electrode, which has a capacity of only 372 mAh g -1 Despite its theoretical capacity, lithium-ion batteries suffer from a significant drawback: low energy density. Furthermore, the organic liquid electrolytes used in these batteries are flammable and prone to leakage, which can easily lead to serious safety incidents. Furthermore, the rigid electrodes, current collectors, and liquid electrolytes make it difficult to achieve flexibility in lithium-ion batteries, making them unable to meet market demands for flexible and wearable devices.

[0003] In response to the many problems of traditional lithium-ion batteries, an effective solution is to replace organic liquid electrolytes with solid electrolytes. Solid electrolytes are non-flammable and stable in air, and have greatly improved safety compared to liquid electrolytes. In addition, the use of solid electrolytes has the lowest chemical potential (-3.04V) and the highest theoretical capacity (3860mAh g -1 ) can be used directly as the negative electrode. Solid electrolytes are currently divided into two categories: organic polymer solid electrolytes and inorganic ceramic solid electrolytes. Polymer solid electrolytes are simple to prepare and have excellent mechanical flexibility. However, they have low ionic conductivity at room temperature and a narrow electrochemical stability window, which makes it difficult to meet the requirements of battery use. Ceramic solid electrolytes can also be subdivided into sulfide-type ceramic solid electrolytes and oxide-type ceramic solid electrolytes. Sulfide electrolytes have high lithium ion conductivity at room temperature (10 -2 S cm -1 ), however, it is very unstable at room temperature, which brings many inconveniences to mass production and commercial use. Oxide solid electrolytes have high ionic conductivity at room temperature (10 -4 S cm -1 ) and is stable in the atmosphere and water. Unfortunately, oxide ceramic solid electrolytes are rigid and brittle, and there is high interface resistance between the electrode and the electrolyte, which cannot meet the requirements of flexibility. Summary of the Invention

[0004] The purpose of the present invention is to provide a method for preparing an oxide-type ceramic fabric composite solid electrolyte using EDTA-modified cotton cloth as a sacrificial template. This method solves the problem that pure cotton cloth has only a small amount of hydroxyl groups and cannot adsorb metal ions well.

[0005] The technical solution adopted by the present invention to solve its technical problem is:

[0006] A method for preparing an oxide-type ceramic fabric composite solid electrolyte using EDTA-modified cotton cloth as a sacrificial template, the method comprising the following steps:

[0007] S1. Modification of cotton cloth: clean cotton cloth was activated in a 10% ± 5% NaOH aqueous solution for 24 h, and then washed with water until neutral;

[0008] The activated cotton was placed in an ethanol-water solution with a volume concentration of 50-60%, stirred for 1-2 hours, APTES was added at a dosage of 30-35 g / L of solution, stirred at 30°C-50°C for 4-5 hours, and washed with ethanol and DMF alternately for multiple times;

[0009] Then, the cotton cloth was placed in a 3-5 g / L EDTAD solution in DMF, stirred at 60-75 ° C for 24 h, and washed with DMF, water, 1-5 wt% NaHCO3 aqueous solution, and water in sequence until the cotton cloth became neutral;

[0010] Finally, the cotton cloth was freeze-dried at -50°C to -60°C and vacuum at 20±5Pa to obtain EDTA-modified cotton cloth;

[0011] S2. Preparation of metal ion precursor solution for oxide-type ceramic solid electrolyte;

[0012] S3. Preparation of oxide-type ceramic fabrics:

[0013] Immerse the EDTA-modified cotton cloth obtained in S1 in the precursor solution obtained in S2, stir thoroughly at 50-70°C, rinse with anhydrous ethanol, and dry;

[0014] The cotton fabric impregnated with the precursor solution is placed in a tube furnace and calcined in air at 700-900°C for 2-6 hours. After natural cooling, the oxide ceramic fabric is obtained and placed in an argon environment for later use.

[0015] S4. Preparation of organic polymer solid electrolyte solution;

[0016] S5. Preparation of oxide-type ceramic fabric composite solid electrolyte:

[0017] Use a syringe to draw up the organic polymer solid electrolyte solution of S4 and pour it into the mold;

[0018] The oxide-type ceramic fabric obtained in S3 is placed on a polytetrafluoroethylene mold covered with a polymer solution, and then a layer of organic polymer solid electrolyte solution is poured to form a sandwich structure;

[0019] After the acetonitrile in the organic polymer solid electrolyte solution is completely volatilized, the composite solid electrolyte cotton cloth is removed and dried at 40-70° C. for 12-48 hours to obtain an oxide-type ceramic fabric composite solid electrolyte.

[0020] The method first activates clean cotton cloth with a sodium hydroxide solution, then grafts amino groups onto the cotton surface using the silane coupling agent APTES, and then modifies the cotton cloth with EDTA. Finally, a metal ion precursor solution for a certain type of oxide-type ceramic fabric is prepared. The modified cotton cloth is impregnated with the precursor solution and calcined at high temperature to produce the oxide-type ceramic fabric. Finally, a polymer electrolyte containing a "polymer conductive lithium salt" system is poured into the fabric to produce the oxide-type ceramic fabric composite solid electrolyte. This material can be used in flexible solid-state lithium batteries and exhibits excellent electrochemical performance and mechanical flexibility.

[0021] The present invention achieves the goal of increasing the lithium ion transfer rate and thus the lithium ion conductivity by increasing the ceramic content in the composite solid electrolyte while maintaining a continuous 3D ion transport path. Cotton, as a natural plant fiber, has high water absorption and excellent mechanical strength. Furthermore, cotton modified with EDTA exhibits excellent adsorption properties for metal ions. This is because the two amino nitrogens and four carboxyl oxygen groups in the EDTA molecule can donate electron pairs to form coordination bonds with metal ions, forming stable coordination compounds. These advantages make EDTA-modified cotton very suitable as a template for the preparation of oxide ceramic materials.

[0022] The present invention combines the advantages of both organic and inorganic solid electrolytes, and is an ideal choice for preparing composite solid electrolytes. Silk, as a natural protein fiber, contains abundant polar amino acids in its fibroin. The negatively charged functional amino acid residues such as -OH and -COOH in these polar amino acids can adsorb metal ions through electrostatic action; however, pure cotton cloth is a natural plant fiber with only a small amount of hydroxyl groups, which cannot achieve the purpose of adsorbing metal ions. The metal adsorbent EDTA was grafted onto cotton cloth and used as a template to prepare a structurally stable LLZO ceramic fabric and a double-layer cast structure LLZO ceramic fabric composite solid electrolyte. This three-dimensional ceramic structure obviously plays a role in uniformly dispersing inorganic ceramic particles, and is conducive to lithium ion conduction. Its thin thickness also promotes the improvement of ionic conductivity and energy density.

[0023] The cotton fabric of the present invention may have a plain weave, a twill weave, a satin weave, a rib weave, or the like, and any of these may be used.

[0024] Preferably, S2, configuration of the metal ion precursor solution of the oxide-type ceramic solid electrolyte: dissolving the metal ion precursor salt containing the oxide-type ceramic solid electrolyte in an appropriate amount of acetic acid-anhydrous ethanol solution, adding an appropriate amount of a heterogeneous atom precursor salt as a dopant, and stirring at room temperature to form a uniform solution;

[0025] The metal ion precursor salt is selected from Li salt, La salt and Zr salt, and the heteroatom precursor salt is selected from Al salt, Nb salt or Ta salt.

[0026] Preferably, S4, the preparation of the organic polymer solid electrolyte solution:

[0027] A polymer and a conductive lithium salt that can be used as a solid electrolyte are selected and vacuum dried within a temperature range below their respective melting points before use;

[0028] The polymer and the conductive lithium salt are dissolved in acetonitrile and stirred sufficiently at room temperature to form a uniformly mixed organic polymer solid electrolyte solution.

[0029] Preferably, in S3, the stirring time is 2-6 hours, and the cotton cloth calcining time is 2-4 hours.

[0030] Preferably, the polymer described in S4 is a mixture of one or more polymers selected from polyethylene oxide (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVDF), and polyvinyl chloride (PVC).

[0031] The conductive lithium salt is selected from one or more of lithium halide (LiX, X=F, Cl, Br, I), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6) or lithium tetrafluoroborate (LiBF4).

[0032] Preferably, the total thickness of the composite solid electrolyte cotton cloth in S5 is maintained at 150 μm-200 μm. The total thickness of the composite solid electrolyte cotton cloth is generally maintained at 150 μm-200 μm. The thickness of each layer is difficult to control because the PEO-LiClO4 polymer solid electrolyte solution will penetrate into the ceramic fabric and finally form a whole.

[0033] Preferably, the content of acetic acid in S2 in the acetic acid-anhydrous ethanol solution is 5-25 vol.%;

[0034] The polymer and the conductive lithium salt in S4 are stirred in acetonitrile for 24-48 h;

[0035] The drying temperature of the composite solid electrolyte cotton cloth in S5 is 50-60° C., and the drying time is 24-48 hours.

[0036] Preferably, the oxide-type ceramic solid electrolyte metal ion precursor solution in S2 is: 49 mmol LiNO3, 21 mmol La(NO3)3·6H2O, 14 mmol ZrO(NO3)3·6H2O dissolved in 40 mL of anhydrous ethanol containing 5 vol.% acetic acid, and 1.75 mmol Al(NO3)3·9H2O is added as an Al additive.

[0037] An oxide-type ceramic fabric composite solid electrolyte prepared by the method of the present invention.

[0038] An application of the oxide-type ceramic fabric composite solid electrolyte described in the present invention in the preparation of flexible solid-state lithium batteries.

[0039] The present invention has the following beneficial effects: first, cotton fabric is graft-modified with EDTA, followed by a metal ion precursor solution of a certain crystal form of oxide-type ceramic fabric; then, the modified cotton fabric is impregnated with the precursor solution and calcined at high temperature to produce the oxide-type ceramic fabric; finally, a polymer electrolyte of a "polymer-conductive lithium salt" system is poured to produce the oxide-type ceramic fabric composite solid electrolyte, which can be used in the energy storage field of flexible lithium batteries. The oxide-type ceramic fabric composite solid electrolyte obtained by this method can be used in lithium batteries and exhibits excellent electrochemical performance and mechanical flexibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 1 is a line sweep voltammetry (LSV) diagram of a Li / solid electrolyte / stainless steel battery containing the Al-LLZO ceramic fabric composite solid electrolyte prepared in Example 1;

[0041] Figure 2 is a scanning electron microscope (SEM) photograph of the Nb-LLZO ceramic fabric prepared in Example 2;

[0042] Figure 3 is a scanning electron microscope (SEM) photograph of the Ta-LLZO ceramic fabric prepared in Example 3;

[0043] Figure 4 is a scanning electron microscope (SEM) photograph of the Ta-LLZO ceramic fabric composite solid electrolyte prepared in Example 3;

[0044] Figure 5 This is an electrochemical impedance spectroscopy (EIS) graph of a stainless steel / solid electrolyte / stainless steel symmetrical cell of the Ta-LLZO ceramic fabric composite solid electrolyte prepared in Example 4;

[0045] Figure 61 is a cycle performance diagram of a Li / solid electrolyte / Li symmetrical battery of the LLTO ceramic fabric composite solid electrolyte prepared in Example 5;

[0046] Figure 7 This is an electrochemical impedance spectroscopy (EIS) graph of a stainless steel / solid electrolyte / stainless steel symmetrical cell of the LLTO ceramic fabric composite solid electrolyte prepared in Example 5. DETAILED DESCRIPTION

[0047] The technical solution of the present invention is further described in detail below through specific examples. It should be understood that the implementation of the present invention is not limited to the following examples, and any form of modification and / or change made to the present invention will fall within the scope of protection of the present invention.

[0048] In the present invention, unless otherwise specified, all parts and percentages are by weight, and the equipment and raw materials used are commercially available or commonly used in the art. The methods in the following examples are all conventional methods in the art unless otherwise specified.

[0049] Ethylenediaminetetraacetic dianhydride (EDTAD), 99%, purchased from MACKLIN;

[0050] Dimethylformamide (DMF), ≥99.5%, purchased from Hangzhou Gaojing Fine Chemical Co., Ltd.;

[0051] 3-Aminopropyltriethoxysilane (APTES), 99%, purchased from MACKLIN.

[0052] Example 1

[0053] A method for preparing an oxide-type ceramic fabric composite solid electrolyte using EDTA-modified cotton cloth as a sacrificial template, the specific steps of the method are as follows:

[0054] (1) Modification of cotton cloth: A piece of cleaned satin-structured cotton cloth was placed in a 10% mass concentration NaOH aqueous solution for activation for 24 hours, and then washed with ultrapure water until neutral. The activated cotton cloth was placed in 300 mL of a 50% volume concentration ethanol aqueous solution, stirred for 1 hour, 9 g of APTES reagent was added, stirred at 30°C for 4 hours, washed with ethanol, and repeatedly washed with DMF. The cotton cloth was then placed in a beaker containing 0.3 g of EDTAD and 100 mL of DMF, stirred at 60°C for 24 hours, and washed four times with DMF, ultrapure water, 2% NaHCO3 aqueous solution, and ultrapure water, respectively, until the cotton cloth was neutral. Finally, the cotton cloth was freeze-dried at -50°C and vacuum 20 Pa for 12 hours;

[0055] (2) Preparation of metal ion precursor solution for oxide (garnet type) ceramic fabric: 49 m mol LiNO3, 21 mmol La(NO3)3·6H2O, and 14 m mol ZrO(NO3)3·6H2O were dissolved in 40 mL of anhydrous ethanol containing 5 vol.% acetic acid, and 1.75 m mol Al(NO3)3·9H2O was added as an Al additive. The mixture was stirred at room temperature for 24 h to form a homogeneous solution to obtain a precursor solution.

[0056] (3) Preparation of oxide (garnet type) ceramic fabric: The cotton fabric modified by EDTA grafting was immersed in the precursor solution in step (2) and stirred at 50°C for 24 hours. After being taken out, it was rinsed with anhydrous ethanol and dried. Finally, the modified cotton fabric immersed in the precursor solution was placed in a tube furnace and calcined at 700°C in air for 4 hours. After natural cooling, it was taken out and placed in a glove box filled with argon for standby use to obtain Al-doped Li7La3Zr2O 12 (Al-LLZO) ceramic fabric. The line sweep voltammetry (LSV) diagram of Li / solid electrolyte / stainless steel battery with Al-LLZO ceramic fabric composite solid electrolyte is shown in the figure. Figure 1 As shown, the battery has a wide electrochemical window at 50 °C.

[0057] (4) Preparation of organic polymer solid electrolyte solution: First, poly(ethylene oxide) (PEO) was dried at 50°C and lithium perchlorate (LiClO4) was dried under vacuum at 100°C for 24 h for later use; then, the two were dissolved in acetonitrile at a molar ratio of EO:Li=10:1, and finally, stirred at room temperature for 48 h to form a uniform mixed solution, thereby obtaining a PEO-LiClO4 polymer solid electrolyte solution.

[0058] (5) Preparation of oxide (garnet type) ceramic fabric composite solid electrolyte: First, the PEO-LiClO4 polymer solid electrolyte solution in step (4) was drawn into a syringe and poured into a polytetrafluoroethylene mold; then, the Al-LLZO ceramic fabric obtained in step (3) was placed on the polytetrafluoroethylene mold covered with the polymer solution, and a layer of PEO-LiClO4 polymer solid electrolyte solution was poured to form a sandwich structure; finally, after the acetonitrile in the PEO-LiClO4 polymer solid electrolyte solution was completely evaporated, the composite solid electrolyte cotton cloth was removed and vacuum dried at 50°C for 24 hours to obtain the final Al-LLZO ceramic fabric composite solid electrolyte. The total thickness of the composite solid electrolyte cotton cloth was controlled to be 150-200 μm.

[0059] Example 2

[0060] A method for preparing an oxide-type ceramic fabric composite solid electrolyte using EDTA-modified cotton cloth as a sacrificial template, the specific steps of the method are as follows:

[0061] (1) Modification of cotton cloth: Place a piece of cleaned twill cotton cloth in a 10% mass concentration NaOH aqueous solution for activation for 24 hours, and then wash it with ultrapure water until it is neutral. Place the activated cotton cloth in 300 mL of a 50% volume concentration ethanol aqueous solution, stir for 1 hour, add 9 g of APTES reagent, stir for 4 hours at 30°C, wash with ethanol, and wash repeatedly with DMF. Then place the cotton cloth in a beaker containing 0.3 g of EDTAD and 100 mL of DMF, stir for 24 hours at 60°C, and wash four times with DMF, ultrapure water, 2% NaHCO3 aqueous solution, and ultrapure water, respectively, until the cotton cloth is neutral. Finally, freeze-dry the cotton cloth at -50°C and vacuum 20 Pa for 12 hours;

[0062] (2) Preparation of metal ion precursor solution for oxide (garnet type) ceramic fabric: 45.5 m mol LiNO3, 21 mmol La(NO3)3·6H2O, and 10.5 m mol ZrO(NO3)3·6H2O were dissolved in 40 mL of anhydrous ethanol containing 10 vol.% acetic acid, and 3.5 m mol NbCl5 was added as a Nb additive. The solution was stirred at room temperature for 24 h to form a homogeneous solution to obtain a precursor solution.

[0063] (3) Preparation of oxide (garnet type) ceramic fabric: The cotton fabric modified by EDTA grafting was immersed in the precursor solution in step (2) and stirred at 50°C for 24 hours. After being taken out, it was rinsed with anhydrous ethanol and dried. Finally, the modified cotton fabric immersed in the precursor solution was placed in a tube furnace and calcined at 800°C in air for 2.5 hours. After natural cooling, it was taken out and placed in a glove box filled with argon for standby use to obtain Nb-doped Li7La3Zr2O 12 (Nb-LLZO) ceramic fabric. Scanning electron microscope (SEM) photos of Nb-LLZO ceramic fabric are shown in Figure 2 .

[0064] (4) Preparation of organic polymer solid electrolyte solution: First, poly(ethylene oxide) (PEO) was dried at 50°C and lithium perchlorate (LiClO4) was dried under vacuum at 100°C for 24 h for later use; then, the two were dissolved in acetonitrile at a molar ratio of EO:Li=15:1, and finally, stirred at room temperature for 48 h to form a uniform mixed solution, thereby obtaining a PEO-LiClO4 polymer solid electrolyte solution.

[0065] (5) Preparation of oxide (garnet type) ceramic fabric composite solid electrolyte: First, the PEO-LiClO4 polymer solid electrolyte solution in step (4) was drawn into a syringe and poured into a polytetrafluoroethylene mold; then, the Nb-LLZO ceramic fabric obtained in step (3) was placed on the polytetrafluoroethylene mold covered with the polymer solution, and a layer of PEO-LiClO4 polymer solid electrolyte solution was poured to form a sandwich structure; finally, after the acetonitrile in the PEO-LiClO4 polymer solid electrolyte solution was completely evaporated, the composite solid electrolyte cotton cloth was removed and vacuum dried at 60°C for 24 hours to obtain the final Nb-LLZO ceramic fabric composite solid electrolyte. The total thickness of the composite solid electrolyte cotton cloth was controlled to be 150-200 μm.

[0066] Example 3

[0067] A method for preparing an oxide-type ceramic fabric composite solid electrolyte using EDTA-modified cotton cloth as a sacrificial template, the specific steps of the method are as follows:

[0068] (1) Modification of cotton cloth: Place a cleaned plain-woven cotton cloth in a 10% mass concentration NaOH aqueous solution for activation for 24 hours, and then wash it with ultrapure water until it is neutral. Place the activated cotton cloth in 300 mL of a 50% volume concentration ethanol aqueous solution, stir for 1 hour, add 9 g of APTES reagent, stir for 4 hours at 30°C, wash with ethanol, and wash repeatedly with DMF. Then place the cotton cloth in a beaker containing 0.3 g of EDTAD and 100 mL of DMF, stir for 24 hours at 60°C, and wash four times with DMF, ultrapure water, 2% NaHCO3 aqueous solution, and ultrapure water, respectively, until the cotton cloth is neutral. Finally, freeze-dry the cotton cloth at -50°C and vacuum 20 Pa for 12 hours;

[0069] (2) Preparation of metal ion precursor solution for oxide (garnet type) ceramic fabric: 45.5 m mol LiNO3, 21 mmol La(NO3)3·6H2O, and 10.5 m mol ZrO(NO3)3·6H2O were dissolved in 40 mL of anhydrous ethanol containing 10 vol.% acetic acid, and 3.5 m mol TaCl5 was added as a Ta additive. The mixture was stirred at room temperature for 24 h to form a homogeneous solution to obtain a precursor solution.

[0070] (3) Preparation of oxide (garnet type) ceramic fabric: The cotton fabric modified by EDTA grafting was immersed in the precursor solution in step (2) and stirred at 50°C for 24 hours. After being taken out, it was rinsed with anhydrous ethanol and dried. Finally, the modified cotton fabric immersed in the precursor solution was placed in a tube furnace and calcined at 800°C in air for 2.5 hours. After natural cooling, it was taken out and placed in a glove box filled with argon for standby use to obtain Ta-doped Li7La3Zr2O 12(Ta-LLZO) ceramic fabric. Scanning electron microscope (SEM) photos of Ta-LLZO ceramic fabric are shown in Figure 3 .

[0071] (4) Preparation of organic polymer solid electrolyte solution: First, poly(ethylene oxide) (PEO) was dried at 50°C and lithium perchlorate (LiClO4) was dried under vacuum at 100°C for 24 h for later use; then, the two were dissolved in acetonitrile at a molar ratio of EO:Li=8:1, and finally, stirred at room temperature for 48 h to form a uniform mixed solution, thereby obtaining a PEO-LiClO4 polymer solid electrolyte solution.

[0072] (5) Preparation of oxide (garnet type) ceramic fabric composite solid electrolyte: First, use a syringe to absorb the PEO-LiClO4 polymer solid electrolyte solution in step (4) and pour it into a polytetrafluoroethylene mold; then, place the Ta-LLZO ceramic fabric obtained in step (3) on the polytetrafluoroethylene mold covered with the polymer solution, and then pour a layer of PEO-LiClO4 polymer solid electrolyte solution to form a sandwich structure; finally, after the acetonitrile in the PEO-LiClO4 polymer solid electrolyte solution is completely evaporated, remove the composite solid electrolyte cotton cloth, and vacuum dry it at 60°C for 24 hours to obtain the final Ta-LLZO ceramic fabric composite solid electrolyte. The total thickness of the composite solid electrolyte cotton cloth is controlled to be 180-220μm. The SEM photo of the Ta-LLZO ceramic fabric composite solid electrolyte is shown in Figure 4 .

[0073] Depend on Figure 2 and Figure 3 It can be seen that the morphology of the ceramic fabric obtained is different due to the different fabric structures of the modified cotton template.

[0074] Example 4

[0075] A method for preparing an oxide-type ceramic fabric composite solid electrolyte using EDTA-modified cotton cloth as a sacrificial template, the specific steps of the method are as follows:

[0076] (1) Modification of cotton cloth: Place a cleaned ribbed cotton cloth in a 10% mass concentration NaOH aqueous solution for activation for 24 hours, and then wash it with ultrapure water until it is neutral. Place the activated cotton cloth in 300 mL of a 50% volume concentration ethanol aqueous solution, stir for 1 hour, add 9 g of APTES reagent, stir for 4 hours at 30°C, wash with ethanol, and wash repeatedly with DMF. Then place the cotton cloth in a beaker containing 0.3 g of EDTAD and 100 mL of DMF, stir for 24 hours at 60°C, and wash four times with DMF, ultrapure water, 2% NaHCO3 aqueous solution, and ultrapure water, respectively, until the cotton cloth is neutral. Finally, freeze-dry the cotton cloth at -50°C and vacuum 20 Pa for 12 hours;

[0077] (2) Preparation of metal ion precursor solution for oxide (garnet type) ceramic fabric: 45.5 m mol LiNO3, 21 mmol La(NO3)3·6H2O, and 10.5 m mol ZrO(NO3)3·6H2O were dissolved in 40 mL of anhydrous ethanol containing 10 vol.% acetic acid, and 3.5 m mol TaCl5 was added as a Ta additive. The mixture was stirred at room temperature for 24 h to form a homogeneous solution to obtain a precursor solution.

[0078] (3) Preparation of oxide (garnet type) ceramic fabric: The cotton fabric modified by EDTA grafting was immersed in the precursor solution in step (2) and stirred at 70°C for 24 hours. After being taken out, it was rinsed with anhydrous ethanol and dried. Finally, the modified cotton fabric immersed in the precursor solution was placed in a tube furnace and calcined at 900°C in air for 1.5 hours. After natural cooling, it was taken out and placed in a glove box filled with argon for standby use to obtain Ta-doped Li7La3Zr2O 12 (Ta-LLZO) ceramic fabric.

[0079] (4) Preparation of organic polymer solid electrolyte solution: First, polyvinylidene fluoride (PVDF) was dried at 80°C and lithium perchlorate (LiClO4) was dried under vacuum at 100°C for 24 h for later use; then, the two were dissolved in acetonitrile at a molar ratio of EO:Li=3:1, and finally, stirred at room temperature for 48 h to form a uniform mixed solution, thereby obtaining a PEO-LiClO4 polymer solid electrolyte solution.

[0080] (5) Preparation of oxide (garnet type) ceramic fabric composite solid electrolyte: First, the PEO-LiClO4 polymer solid electrolyte solution in step (4) was drawn into a syringe and poured into a polytetrafluoroethylene mold; then, the Ta-LLZO ceramic fabric obtained in step (3) was placed on the polytetrafluoroethylene mold covered with the polymer solution, and a layer of PEO-LiClO4 polymer solid electrolyte solution was poured to form a sandwich structure; finally, after the acetonitrile in the PEO-LiClO4 polymer solid electrolyte solution was completely evaporated, the composite solid electrolyte cotton cloth was removed and vacuum dried at 60°C for 24 hours to obtain the final Ta-LLZO ceramic fabric composite solid electrolyte. The total thickness of the composite solid electrolyte cotton cloth was controlled to be 190-230 μm.

[0081] The electrochemical impedance spectroscopy (EIS) of the stainless steel / solid electrolyte / stainless steel symmetrical cell of the Ta-LLZO ceramic fabric composite solid electrolyte prepared in this embodiment is shown in FIG. Figure 5 .

[0082] Example 5

[0083] A method for preparing an oxide-type ceramic fabric composite solid electrolyte using EDTA-modified cotton cloth as a sacrificial template, the specific steps of the method are as follows:

[0084] (1) Modification of cotton cloth: Place a piece of cleaned twill cotton cloth in a 10% mass concentration NaOH aqueous solution for activation for 24 hours, and then wash it with ultrapure water until it is neutral. Place the activated cotton cloth in 300 mL of a 50% volume concentration ethanol aqueous solution, stir for 1 hour, add 9 g of APTES reagent, stir for 4 hours at 30°C, wash with ethanol, and wash repeatedly with DMF. Then place the cotton cloth in a beaker containing 0.3 g of EDTAD and 100 mL of DMF, stir for 24 hours at 60°C, and wash four times with DMF, ultrapure water, 2% NaHCO3 aqueous solution, and ultrapure water, respectively, until the cotton cloth is neutral. Finally, freeze-dry the cotton cloth at -50°C and vacuum 20 Pa for 12 hours;

[0085] (2) Preparation of metal ion precursor solution for oxide (perovskite) ceramic fabric: 23.1 m mol LiNO3, 38.9 m mol La(NO3)3·6H2O, and 70 m mol Ti(OC4H9) were dissolved in 40 mL of anhydrous ethanol containing 15 vol.% acetic acid, and 3.5 m mol NbCl5 was added as a Nb additive. The mixture was stirred at room temperature for 24 h to form a homogeneous solution to obtain a precursor solution.

[0086] (3) Preparation of oxide (perovskite) ceramic fabric: The cotton fabric modified by EDTA grafting was immersed in the precursor solution in step (2), and stirred at 70°C for 24 hours. After taking it out, it was rinsed with anhydrous ethanol and dried. Finally, the modified cotton fabric immersed in the precursor solution was placed in a tube furnace, calcined at 800°C in air for 2.5 hours, and after natural cooling, it was taken out and placed in a glove box filled with argon for standby use to obtain Nb-doped Li 3x La (2 / 3)-x TiO3(LLTO) ceramic fabric.

[0087] (4) Preparation of organic polymer solid electrolyte solution: First, polyacrylonitrile was dried at 60°C and lithium perchlorate (LiClO4) was dried under vacuum at 100°C for 24 h for later use; then, the two were dissolved in acetonitrile at a molar ratio of PAN:LiTFSI = 3:1, and finally, stirred at room temperature for 48 h to form a uniform mixed solution, thereby obtaining a PAN-LiClO4 polymer solid electrolyte solution.

[0088] (5) Preparation of oxide (garnet type) ceramic fabric composite solid electrolyte: First, the PAN-LiClO4 polymer solid electrolyte solution in step (4) is drawn into a syringe and poured into a polytetrafluoroethylene mold; then, the LLTO ceramic fabric obtained in step (3) is placed on the polytetrafluoroethylene mold covered with the polymer solution, and a layer of PAN-LiClO4 polymer solid electrolyte solution is poured to form a sandwich structure; finally, after the acetonitrile in the PEO-LiClO4 polymer solid electrolyte solution is completely evaporated, the composite solid electrolyte cotton cloth is removed and vacuum dried at 60°C for 24 hours to obtain the final LLTO ceramic fabric composite solid electrolyte.

[0089] The cycle performance diagram of the Li / solid electrolyte / Li symmetrical battery of the LLTO ceramic fabric composite solid electrolyte prepared in this embodiment is shown in FIG. Figure 6 ; Electrochemical impedance spectroscopy (EIS) of stainless steel / solid electrolyte / stainless steel symmetric cell with LLTO ceramic fabric composite solid electrolyte is shown in Figure 7 .Depend on Figure 5 and Figure 7 It can be seen that when the crystal types of ceramic fabrics are different, the ionic conductivity of their composite solid electrolytes is also different.

[0090] Analysis of micrograph results

[0091] The SEM images of the oxide garnet ceramic fabrics obtained in Examples 2 and 3 are shown in FIG. Figure 2 and 3 As shown. After the cotton template is adsorbed, only a few yarns are broken, and the rest are structurally intact. There are breaks between the ceramic yarns and between the ceramic fibers, and the gaps are enlarged. This is determined by the characteristics of the cotton cloth's woven structure. Cotton fibers and cotton fibers twist with each other to form cotton yarns, and cotton yarns and cotton yarns form cotton cloth according to a certain weaving structure. Therefore, cracks and gaps are formed in the ceramic fabric after air calcination. These gaps provide convenience for the subsequent PEO-LiTFSI solution to fully penetrate into the ceramic fabric. At the same time, due to the different types of cotton fabric templates, the morphology of the ceramic fabrics derived therefrom is also different.

[0092] The scanning electron microscope (SEM) photograph of the Ta-LLZO ceramic fabric composite solid electrolyte prepared in Example 3 is as follows: Figure 4 As shown, the fabric fibers and the casting liquid are tightly bonded, forming a continuous electrode / electrolyte interface. Furthermore, the double-layer casting structure facilitates the full infiltration of the polymer into the ceramic fabric, allowing them to bond more tightly and fully. This enhances mechanical strength and effectively prevents lithium dendrite penetration. Furthermore, the increased electrolyte thickness improves ionic conductivity.

[0093] Comparative Example

[0094] A method for preparing oxide-type ceramic fabrics using EDTA-modified cotton cloth as a sacrificial template, the method comprising the following specific steps:

[0095] (1) Preparation of metal ion precursor solution for oxide (garnet type) ceramic fabric: 49 m mol LiNO3, 21 mmol La(NO3)3·6H2O, and 14 m mol ZrO(NO3)3·6H2O were dissolved in 40 mL of anhydrous ethanol containing 5 vol.% acetic acid, and 1.75 m mol Al(NO3)3·9H2O was added as an Al additive. The mixture was stirred at room temperature for 24 h to form a homogeneous solution to obtain a precursor solution.

[0096] (2) Preparation of oxide (garnet type) ceramic fabric: Pure cotton cloth was immersed in the precursor solution in step (1) and stirred at 50°C for 24 hours. After being taken out, it was rinsed with anhydrous ethanol and dried. Finally, the modified cotton cloth immersed in the precursor solution was placed in a tube furnace and calcined at 700°C in air for 4 hours. Since there were only a few hydroxyl groups on the pure cotton cloth, it could not adsorb metal ions well. Therefore, the cotton cloth template was calcined completely and Al-doped Li7La3Zr2O was not successfully obtained. 12 (Al-LLZO) ceramic fabric.

[0097] Application Examples

[0098] The oxide-based ceramic fabric composite solid electrolyte described in the present invention is used to prepare flexible solid-state lithium batteries. Full batteries were assembled using this solid electrolyte, and their electrochemical properties were tested.

[0099] The parameters of the positive electrode-solid electrolyte / Li full battery are as follows: 2032 button cells are assembled in a glove box, from top to bottom: negative electrode shell → spring → gasket → lithium sheet → integrated electrode-electrolyte → positive electrode shell. The full battery cycle performance is 34mA g -1 Impedance measurements were performed on a Zennium-ECW (electrochemical workstation).

[0100] The line sweep voltammetry (LSV) diagram of the Li / solid electrolyte / stainless steel battery of the Al-LLZO ceramic composite nanofiber solid electrolyte prepared in Example 1 is as follows: Figure 1 As shown, the battery has a wide electrochemical window (5.1 V) at 50 °C.

[0101] The EIS of the stainless steel / solid electrolyte / stainless steel symmetric cells of Ta-LLZO and LLTO ceramic fabric composite solid electrolytes prepared in Examples 4 and 5 are shown as follows: Figure 5 and 7As shown in the figure, as the test temperature increases, the ionic conductivity of the composite solid electrolyte also increases. Among them, the ionic conductivity of the Ta-LLZO ceramic fabric composite solid electrolyte at 30°C is 4.7×10 -5 S cm -1 , the LLTO ceramic fabric composite solid electrolyte is 6×10 -6 S cm -1 The high ionic conductivity is attributed to the fact that the 3D ceramic fabric network can provide long-distance continuous ion conductive paths. In addition, the ionic conductivity of the garnet-type ceramic fabric composite solid electrolyte is higher than that of the perovskite type, which is attributed to the fact that the garnet-type ceramic fabric is doped with heteroatoms, which can optimize the electrochemical performance.

[0102] The cycle performance of the Li / solid electrolyte / Li symmetrical battery of the LLTO ceramic fabric composite solid electrolyte prepared in Example 5 is shown in FIG. Figure 6 As shown in the figure, the symmetrical battery -2 It can cycle stably for 430 h without short circuit at a current density of 100 mV, and its voltage platform is only 40 mV, which indicates the excellent interface stability between Ta-LLZO ceramic fabric composite solid electrolyte and lithium metal.

[0103] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on its differences from the other embodiments. Reference can be made to the descriptions of the identical or similar parts between the various embodiments. For the devices disclosed in the embodiments, since they correspond to the methods disclosed in the embodiments, the descriptions are relatively simple, and the relevant parts can be referred to the descriptions of the methods.

[0104] The above is a detailed introduction to the method for preparing an oxide-type ceramic fabric composite solid electrolyte using EDTA-modified cotton cloth as a sacrificial template provided by the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core concept. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, the present invention can also be improved and modified in a number of ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing oxide-type ceramic fabric composite solid electrolyte using EDTA-modified cotton cloth as a sacrificial template, characterized in that The method comprises the following steps: S1. Modification of cotton cloth: activate the clean cotton cloth in a 10%±5% NaOH aqueous solution for 24 hours, and then wash it with water until it becomes neutral; The activated cotton was placed in an ethanol aqueous solution with a volume concentration of 50-60%, stirred for 1-2 hours, APTES was added, the amount of APTES was 30-35 g / L solution, stirred at 30℃-50℃ for 4-5 hours, washed with ethanol, and washed with DMF alternately for multiple times; Then, the cotton cloth was placed in a 3-5 g / L EDTAD DMF solution, stirred at 60°C-75°C for 24 h, and washed with DMF, water, 1-5 wt% NaHCO3 aqueous solution, and water in sequence until the cotton cloth was neutral; Finally, the cotton cloth was freeze-dried at -50°C to -60°C and vacuum 20±5Pa to obtain EDTA-modified cotton cloth; S2, configuration of metal ion precursor solution of oxide-type ceramic solid electrolyte; S3. Preparation of oxide-type ceramic fabrics: The EDTA-modified cotton cloth obtained in S1 is immersed in the precursor solution obtained in S2, stirred sufficiently at a temperature of 50-70°C, and then rinsed with anhydrous ethanol and dried; The cotton impregnated with the precursor solution is placed in a tube furnace, calcined in air at 700-900°C for 2-6 hours, and after natural cooling, an oxide ceramic fabric is obtained, which is placed in an argon environment for standby use; S4. Preparation of organic polymer solid electrolyte solution; S5. Preparation of oxide-type ceramic fabric composite solid electrolyte: Use a syringe to draw up the organic polymer solid electrolyte solution of S4 and pour it into the mold; The oxide-type ceramic fabric obtained in S3 is placed on a polytetrafluoroethylene mold covered with a polymer solution, and then a layer of organic polymer solid electrolyte solution is poured to form a sandwich structure; After the acetonitrile in the organic polymer solid electrolyte solution is completely volatilized, the composite solid electrolyte cotton cloth is removed and dried at 40-70° C. for 12-48 hours to obtain an oxide-type ceramic fabric composite solid electrolyte.

2. The method according to claim 1, characterized in that: S2. Preparation of metal ion precursor solution of oxide-type ceramic solid electrolyte: dissolving metal ion precursor salt of oxide-type ceramic solid electrolyte in an appropriate amount of acetic acid-anhydrous ethanol solution, adding an appropriate amount of heteroatom precursor salt as a dopant, and stirring at room temperature to form a uniform solution; The metal ion precursor salt is selected from Li salt, La salt and Zr salt, and the heteroatom precursor salt is selected from Al salt, Nb salt or Ta salt.

3. The method according to claim 1, characterized in that: S4. Preparation of organic polymer solid electrolyte solution: A polymer and a conductive lithium salt that can be used as a solid electrolyte are selected and vacuum dried within a temperature range below their respective melting points for later use; The polymer and the conductive lithium salt are dissolved in acetonitrile and stirred sufficiently at room temperature to form a uniformly mixed organic polymer solid electrolyte solution.

4. The method according to claim 1, characterized in that: In S3, the stirring time is 2-6 h, and the cotton cloth calcination time is 2-4 h.

5. The method according to claim 1 or 3, characterized in that: The polymer described in S4 is a mixture of one or more polymers selected from polyethylene oxide (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVDF), and polyvinyl chloride (PVC), The conductive lithium salt is selected from one or more of lithium halides (LiX, X=F, Cl, Br, I), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6) or lithium tetrafluoroborate (LiBF4).

6. The method according to claim 1, characterized in that: The total thickness of the composite solid electrolyte cotton cloth in S5 is maintained at 150 μm-200 μm.

7. The method according to claim 1, characterized in that: The content of acetic acid in S2 in the acetic acid-anhydrous ethanol solution is 5-25 vol.%; The stirring time of the polymer and the conductive lithium salt in acetonitrile in S4 is 24-48h; The drying temperature of the composite solid electrolyte cotton cloth in S5 is 50-60°C, and the drying time is 24-48h.

8. The method according to claim 1, characterized in that: The metal ion precursor solution of the oxide-type ceramic solid electrolyte in S2 is: 49 m mol LiNO3, 21 m mol La(NO3)3∙6H2O, 14 m mol ZrO(NO3)3∙6H2O dissolved in 40 mL of anhydrous ethanol containing 5 vol.% acetic acid, and 1.75 m mol Al(NO3)3∙9H2O was added as an Al additive.

9. An oxide-type ceramic fabric composite solid electrolyte prepared by the method according to claim 1.

10. Use of the oxide-type ceramic fabric composite solid electrolyte according to claim 9 in the preparation of flexible solid-state lithium batteries.

Citation Information

Patent Citations

  • Method for preparing oxide type ceramic fabric composite solid electrolyte by taking silk fabric as sacrificial template

    CN111725562A

  • Preparation method of flexible supercapacitor electrode with excellent electrochemical performance

    CN115064392A